ARAMAIC STUDIES AND THE NEW TESTAMENT: THE UNPUBLISHED WORK OF THE LATE A. J. WENSINCK OF LEYDEN - Black, Matthew (The journal of theological studies, 1948)
M. BLACK; ARAMAIC STUDIES AND THE NEW TESTAMENT: THE UNPUBLISHED WORK OF THE LATE A. J. WENSINCK OF LEYDEN, The Journal of Theological Studies, Volume os-XLIX,